Pengaruh Work Life Balance, Employee Engagement Dan Lingkungan Kerja Islami Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Karyawan Kopontren Baitul Muamalat Al Hikmah Blora - Safitri, Niken Ayu; Soleh, Mohammad (Faculty of Islamic Economics and Business, Madura Islamic State University, 2022)
This study aims to identify the effect of work life balance, employee engagement and Islamic work environment on employee performance with job satisfaction as an intervening variable for employees of the Baitul Muamalat Al Hikmah Blora Kopontren. The method used in this research is a questionnaire. The sample of this study amounted to 55 respondents with purposive sampling technique. The conclusion of this study is that work life balance has a significant positive effect on employee performance, employee engagement has a significant positive effect on employee performance, Islamic work environment has a significant positive effect on employee performance, job satisfaction has a significant positive effect on employee performance, work life balance has a positive effect but not significant effect on employee performance, employee engagement has a positive but not significant effect on employee performance, Islamic work environment has a significant positive effect on employee performance, job satisfaction is able to mediate the effect of work life balance on performance, job satisfaction is able to mediate the effect of employee engagement on performance, job satisfaction is able to mediate the influence of the Islamic work environment on performance.